Buffering capacity of bacilli that grow at different pH ranges. - Krulwich, T A (1985)
Cytoplasmic buffering capacities and buffering by whole cells were examined in six bacterial species: Bacillus acidocaldarius, Bacillus stearothermophilus, Escherichia coli, Bacillus subtilis, Bacillus alcalophilus, and Bacillus firmus RAB. Acid-base titrations were conducted on whole cells and cells permeabilized with Triton X-100 or n-butanol. In all of the species examined, the buffering capacity of intact cells was generally a significant proportion of the total buffering capacity, but the magnitude of the buffering capacity varied from species to species. Over the entire range of pH values from 4 to 9.5, B. subtilis exhibited a cytoplasmic buffering capacity that was much higher than that of B. stearothermophilus, B. acidocaldarius, or E. coli. The latter three species had comparable cytoplasmic buffering capacities at pH 4 to 9.5, as long as optimal conditions for cell permeabilization were employed. All of the nonalkalophiles exhibited a decrease in cytoplasmic buffering capacity as the external pH increased from pH 5 to 7. At alkaline pH values, the two thermophiles in the study had particularly low cytoplasmic buffering capacities, and the two alkalophilic bacteria had appreciably higher cytoplasmic buffering capacities than any of the other species studied. Cytoplasmic buffering capacities as high as 1,100 nmol of H+ per pH unit per mg of protein were observed in alkalophilic B. firmus RAB. Since previous studies have shown that immediate cytoplasmic alkalinization occurs upon loss of the active mechanisms for pH homeostasis in the alkalophiles, the very high buffering capacities apparently offer no global protection of internal pH. Perhaps, the high buffering capacities reflect protective mechanisms for specific macromolecules or process rather than part of the mechanisms for bulk pH homeostasis.